The Multicultural Classroom Phenomenon: Presenting Multicultural Education in English Learning in Indonesia - Rullu, ST. Marhana; Eriyanti , Ribut Wahyu; Asih, Ria Arista (Universitas Terbuka, 2025)
Multicultural education comes as a guideline in creating a learning environment that respects cultural diversity in Indonesia. Integrating multicultural education values in English language learning can increase awareness of diversity and develop cross-cultural communication skills. This investigation seeks to explore the phenomenon of multicultural classrooms with a focus on the enactment of multicultural education values in English language learning in Indonesia. Through a library research approach by analyzing the concept of multicultural education integrated from various data sources in the form of basic regulatory documents, legal bases, study guides, and other supporting articles. The results of the study identified several important values in multicultural education, such as appreciation of the value of diversity, the value of humanity and social justice, the value of unity and integrity, tolerance and mutual respect, collaborative/cooperation, and empathy. This research seeks to offer contributions to the application and discussion of multicultural education both at the national and international levels. Furthermore, this study suggests the need to develop research on the teaching process and assessment of learning outcomes integrated in multicultural education.